The Chinese Television Industry - Keane, Michael (A BFI Book published by Palgrave, 2015)
"Though the television industry in China is enormous, fewer people are watching television screens. In this groundbreaking study, Michael Keene shows how television content is changing, how the Chinese government is responding to the challenges presented by digital media, and how businesses are brokering alliances in both traditional and new media sectors. Keane outlines the process of making content in China, focusing on regulatory institutions, ownership, censorship, programmes and channels, copygright, formats and the role of media bases. Spanning a wide variety of genres, the book examines four models of content internationalisation: licensing of programmes, formats, co-productions and online media. Written in an accessible style by one of the world's leading experts on China's media, this book explores how streamed online content is impacting on the state's control of ideas and management of the traditional broadcasting sector. This is the authoritative text for scholars, students, businesses and policy makers wanting to understand how the rapid evolution of Chinese media aligns with the nation's soft power initiatives"–Back cover.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Asia: New Growth Areas - Keane, Michael (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
The previous chapter introduced in broad brushstrokes the issues at stake in this study, beginning with a critique of globalization and moving on to sketch in ﬁner detail national television systems, the role of local content, and the economic importance of formats. The chapter concluded with a brief overview of the vagaries of copyright law as it applies to formats. Here, we initiate a discussion of Asian television systems beginning with a much different perspective on the ramiﬁcations of cultural borrowing. In this context we note that the format business straddles the divide between creative endeavour and innovation on the one hand, and slavish imitation on the other. This polarization manifests in widespread misunderstanding of the goals of format producers and distributors, and the role that formats play in the shaping of television schedules. We need therefore to ﬂesh out the in-between issues. These are primarily concerned with the relationship between the format and its localization, television consumption within ‘cultural continents’, and changes in media systems. Taking this further we note the relationship between production and reception within Asia, the growth of television industries in the region and the relationship between formatting and new media distribution platforms that use interactive technologies allowing viewers to feedback responses. This exercise enables us to identify an alternative list of conceptual tools to those championed by political economy scholars.
Num Pages: 12
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

A Revolution in Television and a Great Leap Forward for Innovation?: China in the Global Television Format Business - Keane, Michael (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Unlike smaller nation-states in this study the People’s Republic of China has never really countenanced a scarcity of domestic television content. Supply has been constant, indicating both the importance and the sheer size of the sector. The nationalized broadcast media has for several decades churned out cheaply produced ﬁlms, documentaries, dramas, and news programmes. During the last two decades of the twentieth century, however, audience demand for domestic content began to wane as more as more international programmes found their way into schedules, particularly in southern China. China’s accession to the World Trade Organization in December 2001 seemed to herald soul-searching among its media mandarins. What would happen? Would China be inundated by foreign content (the worst case scenario) or would China, as it has done over time, absorb and regulate foreign inﬂuences?
Num Pages: 17
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Civil Society, Regulatory Space and Cultural Authority in China’s Television Industry - Keane, Michael (Television, Regulation and Civil Society in Asia, 2002)
The question of why civil society presents such appeal for commentators, scholars and journalists writing about developing nations is an important one. The most likely explanation is that a kind of global faith exists in civil society as the driving force of a new world order. This global transformation, exemplified by the collapse of the Soviet bloc, celebrates people’s freedom to participate in public discourse, and ultimately in processes of directly electing political representatives. In this sense the concepts of civil society and the public sphere come together to describe a global anti-authoritarian groundswell where the power of ideas is linked to global cultural development.
Num Pages: 5
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

A Revolution in Television and a Great Leap Forward for Innovation?: China in the Global Television Format Business - Keane, Michael (Global Television Formats : Circulating Culture, Producing Identity, 2012)
Livre : For decades, television scholars have viewed global television through the lens of cultural imperialism, focusing primarily on programs produced in the US and UK markets and exported to foreign markets. This book explores how, thanks to recent technological innovation and globalization, television is now finally becoming truly global. Global Television Formats aims to revise the place of the global in television studies. The essays gathered here explore the diversity of global programming and approaches, and ask how to theorize contemporary
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

New Television, Globalisation, and the East Asian Cultural Imagination - Keane, Michael; Fung, Anthony Y. H.; Moran, Albert (Hong Kong University Press, 2007)
This volume is divided into three parts: 'Adaptation and Local Production in East Asia', 'Formats, Clones, and Generic Variations' and 'New Television'.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Chine (corpus analysé); Corée du Sud (corpus analysé); Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); Japon (corpus analysé); Taiwan (corpus analysé); _Nettoyé